1996
DOI: 10.2331/suisan.62.51
|View full text |Cite
|
Sign up to set email alerts
|

Entrance Shape of Fish Trap and Fishing Efficiency.

Abstract: The ingress and escape behavior for a fish trap was studied through experiments in the laborato ry using green fish Girella punctata. The fish behavior for a simplified funnel set in the aquarium was recorded on video tape. An index of structure for various sizes of funnel-shape entrances was in troduced as a means of analyzing the entrapping difficulty. The following results were obtained: The number of fish entrapped was constant when the index was less than 1.0, but decreased when the in dex increased above… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2006
2006
2019
2019

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 0 publications
0
5
0
Order By: Relevance
“…For funnel‐shaped entrances, a structure index has been defined to analyze the difficulty of trapping fish 14 . The ingress index of the commercial trap used in this study was approximately 2.0 (>1.0), suggesting that the entrance shape was not optimal for fish ingress and that catch efficiency could be improved by modifying the shape of the entrance.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…For funnel‐shaped entrances, a structure index has been defined to analyze the difficulty of trapping fish 14 . The ingress index of the commercial trap used in this study was approximately 2.0 (>1.0), suggesting that the entrance shape was not optimal for fish ingress and that catch efficiency could be improved by modifying the shape of the entrance.…”
Section: Discussionmentioning
confidence: 97%
“…Many studies [3][4][5][6][7][8][9][10][11][12][13][14][15] have reported that catch efficiency varies according to trap structure, and that the most important factor is the shape of the trap entrance. However, it is difficult to directly observe fish behavior near the trap entrance commercial actual fishing conditions.…”
Section: Introductionmentioning
confidence: 99%
“…Since the inlet direction is towards the bottom, rather than the front, at these landing angles, it would be hard for conger eels to find and enter the inlet when compared to pots at different angles. As a result, the inclination angle of the funnel in the pot has been reported as a factor that affects the catching performance of other target fish (Sugimoto et al, 1996;Li et al, 2006). Recently, tubular pots are commonly produced using recycled plastic materials, such as polyethylene (PE) or polypropylene (PP), and using mixture of multiple resins in various ratios.…”
Section: Discussionmentioning
confidence: 99%
“…Traps are widely used in fisheries throughout the world because of their simple structure and convenient operation. However, many factors affect the catch rate of traps, and the most important factor is the trap entrance 1–11 . The entrance number, shape, size and location significantly affect the catch.…”
Section: Introductionmentioning
confidence: 99%
“…However, many factors affect the catch rate of traps, and the most important factor is the trap entrance. [1][2][3][4][5][6][7][8][9][10][11] The entrance number, shape, size and location significantly affect the catch. For example, Munro et al .…”
Section: Introductionmentioning
confidence: 99%